Total carbon, total organic carbon, and total inorganic carbon (solid-phase discrete samples) from IODP Hole 389-M0106A - Webster, Jody M; Ravelo, Ana Christina; Grant, Hannah; Stewart, Margaret S; Rydzy, Marisa; Le Ber, Erwan; Allison, Nicola; Asami, Ryuji; Boston, Brian; Braga, Juan-Carlos; Brenner, Logan; Chen, Xuefei; et al. (PANGAEA, 2025)
Total carbon (TC), total organic carbon (TOC), and total inorganic carbon (TIC) content from solid-phase discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai'i, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. During the onshore phase a set of solid-phase samples were taken from the work halves of core sections, with a volume of approx. 10 cubic centimeters each, were taken with the purpose to be later on split into aliquots for the following three analyses: X-ray diffraction, carbon and X-ray fluorescence. Bulk samples were subsequently freeze-dried, ground and homogenized to a fine powder (<20 µm particle size) by ECORD Science Operator staff using a pestle and an agate mortar or a ball mill. Sample aliquots of approx. 100 mg (TC) and 1 g (TOC) were processed through a CS744 LECO carbon-sulfur analyzer to obtain the respective concentrations. TIC was calculated as the difference between TC and TOC. For further methodological information see methods chapter in Webster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025
Keywords: central Pacific; Coral Reef; Earth climate feedbacks; Earth history tipping points; Expedition 389; Hawaiian Drowned Reefs; Hawaiian geology; International Ocean Discovery Program (IODP); MMA Valour; Paleoclimate; sea level; volcanic